2017
DOI: 10.1159/000484146
|View full text |Cite
|
Sign up to set email alerts
|

Points of Concern in Post Acute Kidney Injury Management

Abstract: The incidence of acute kidney injury (AKI) will in the future remain high, partly due to an increase in comorbidities and other AKI favoring factors such as the rise in high-risk diagnostic and therapeutic interventions. AKI has emerged as a major public health concern with high human and financial costs. It has recently been demonstrated that patients surviving an AKI episode show increased all-cause mortality, chronic kidney disease (CKD), ESRD, cardiovascular events, and reduced quality of life. Although it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 58 publications
(70 reference statements)
0
16
0
Order By: Relevance
“…Specific therapies targeted at particular renal conditions (e.g., tolvaptan for adult polycystic kidney disease or preventive measures for kidney stones) were not considered. In addition, AKI and its prevention, although definitely linked to CKD [ 12 ] and thus a likely cause of cardio-vascular complications [ 13 ], was not considered and the reader is referred to specific reviews on this topic [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Specific therapies targeted at particular renal conditions (e.g., tolvaptan for adult polycystic kidney disease or preventive measures for kidney stones) were not considered. In addition, AKI and its prevention, although definitely linked to CKD [ 12 ] and thus a likely cause of cardio-vascular complications [ 13 ], was not considered and the reader is referred to specific reviews on this topic [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies in humans demonstrated an increased risk for CKD and long-term mortality after an AKI episode (Coca et al, 2009;Heung et al, 2016;Vanmassenhove et al, 2018). This increased risk was documented even after milder forms of AKI with apparent fast recovery (Coca et al, 2009;Heung et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study, plasma SDMA was also able to identify dogs with azotemic AKI (Dahlem et al, 2017). In humans, follow-up of renal function after an episode of AKI is advised at least in high-risk patients, because patients surviving an AKI episode have an independently increased risk to develop CKD (Coca et al, 2012;Rimes-Stigare et al, 2015;Heung et al, 2016;Vanmassenhove et al, 2018). Kidney injury biomarkers have the potential to predict renal recovery from AKI in humans (Koraishy and Coca, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…in frail AKI patients 24,32,37 . Fourth, and above all, in view of the frequent link with CKD, the nephrologist can play a role in preventing evolution towards CKD and to steer the approach and follow-up if kidney function does not recover 9,38,39 . Thus, we call not only for European research activity on AKI, but also for clinical involvement of the nephrologist in AKI outside the nephrology unit.…”
Section: )mentioning
confidence: 99%